2005
DOI: 10.1016/j.jinsphys.2004.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Insulin signaling is necessary for vitellogenesis in Drosophila melanogaster independent of the roles of juvenile hormone and ecdysteroids: female sterility of the chico1 insulin signaling mutation is autonomous to the ovary

Abstract: It has been suggested that insulin signaling mutations of Drosophila melanogaster are sterile and long-lived because of juvenile hormone (JH) and ecdysteroid deficiency. However, female sterility of an insulin/IGF-like signaling mutant (chico(1)) of D. melanogaster is not mediated by downstream systemic signaling in terms of major alterations in JH or ecdysteroid levels. chico(1) is a null mutation in the insulin substrate protein (CHICO) gene of D. melanogaster. Homozygous chico(1) females are sterile and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
139
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(149 citation statements)
references
References 49 publications
8
139
1
1
Order By: Relevance
“…17) could be due either to the specifi c gene that was mutated in the insulin signaling pathway (DInR versus chico) or to genetic background. However, the only functional test in this series of studies (reciprocal ovarian transplants between wild-type and chico 1 females) showed that wild-type ovaries produced mature eggs in chico 1 females, whereas chico 1 ovaries did not mature in wild-type individuals [17]. Thus, the systemic factors necessary for egg production are present in homozygous chico 1 individuals.…”
Section: Five Components Of the Cost Of Reproductionmentioning
confidence: 71%
See 1 more Smart Citation
“…17) could be due either to the specifi c gene that was mutated in the insulin signaling pathway (DInR versus chico) or to genetic background. However, the only functional test in this series of studies (reciprocal ovarian transplants between wild-type and chico 1 females) showed that wild-type ovaries produced mature eggs in chico 1 females, whereas chico 1 ovaries did not mature in wild-type individuals [17]. Thus, the systemic factors necessary for egg production are present in homozygous chico 1 individuals.…”
Section: Five Components Of the Cost Of Reproductionmentioning
confidence: 71%
“…Low levels of JH biosynthesis in vitro were also observed in individuals with a mutation in chico, a gene-encoding an insulin substrate protein [16]. However, in a different study [17], fl ies with the same mutation exhibited neither reduced JH biosynthesis nor lowered levels of ecdysteroids [17]. The differences between these studies (Refs 13 and 16 versus Ref.…”
Section: Five Components Of the Cost Of Reproductionmentioning
confidence: 94%
“…Flies were well-fed, but mutant GLCs did not progress into mid oogenesis (Supplementary Figure 1), consistent with previous studies. 7,14,20 To determine the stage of oogenesis in which growth arrested, the last healthy egg chamber at the end of an ovariole was scored (Supplementary Figure 1m). Stage 4 of oogenesis was the predominant stage at which oogenesis arrested for InR 339 (38%), chico 1 (50%), Tor DP (59%), and S6k lÀ1 (54%) GLCs.…”
Section: Resultsmentioning
confidence: 99%
“…In general terms, yolk precursor-encoding genes are downstream of signaling cascades that shorten lifespan in solitary model organisms (4,28,54). IIS is necessary for vitellogenesis in Drosophila (29), and negative effects on longevity have been shown directly for vitellogeninencoding genes that are controlled by IIS in C. elegans (3).…”
Section: Discussionmentioning
confidence: 99%
“…JH is part of the IIS pathway in Drosophila (5) that coregulates yolk peptide expression and somatic maintenance antagonistically (1,4,(28)(29)(30). In C. elegans, reduced activity of the vitellogenin-encoding genes vit-2 and vit-5 (which are downstream of the IIS receptor Daf-2) lengthens lifespan (3).…”
mentioning
confidence: 99%